"Closing the Deal" on the Distributive Negotiation Process - Istabrina Urfa Azyumardiani; Cecep Safa'atul Barkah; Nurillah Novel (JMB : Jurnal Manajemen dan Bisnis, 2023)
Negotiations have always been going on in the business world. Distributive negotiation is a strategy in negotiations that results in one party losing in the form of arguments or material. In the distributive negotiation process, there are 5 types of closing deals, namely Providing Alternatives, Closing Assumptions, Separating Differences, Exploding Offers, and Sweeteners. Women agribusiness entrepreneurs in the city of Bogor use alternatives, Bank BNI Syariah Medan uses alternatives, namely PT Freeport Indonesia Uses Sweeteners, and Indonesian Government Glasses Use ExplosOffersffer. A good closing agreement is a closing agreement that is adapted to the situation during the negotiation process.